Implementation of Role Playing Learning Methods on Ethics and Politeness of Speaking in Elementary Schools: Penerapan Metode Pembelajaran Role Playing Terhadap Etika Dan Kesantunan Berbicara Di Sekolah Dasar - Yanti, Sri Kastatik Apriwa; Surkatiningsih, Wahyu; Hendratno, Hendratno (Madrosatuna: Journal of Islamic Elementary School, 2024)
This study was conducted to determine the application of role-playing learning methods to ethics and the politeness of speaking in elementary schools. In general, this study aims to determine the factors that cause low Role of Ethics and Politeness in students and identify the causes of low Ethics and Politeness in speaking in students so that solutions can be found to improve the Role of Ethics and Politeness in class. This study uses a qualitative approach by defining the research object using data analysis methods. The subjects of the study were 20 fourth-grade students and 2 class teachers. The instruments used in this study were questionnaires and interviews. Based on the data analysis that has been carried out, information can be obtained that the low role of student ethics is the cause of the lack of politeness in speaking and behaving. For this reason, a solution emerged: students must practice speaking and behaving politely through habituation at school, and teachers must often motivate students to speak and praise students who learn role-playing at school. Role-playing learning understands and considers students' interests in knowing their daily speaking and behaving skills. This study shows that implementing role-playing learning methods for students' speaking ethics and politeness is important in shaping students' behavior and actions. Students need to develop a high level of role ethics and politeness because this will make them accustomed to behaving and being polite in the formation of their characters in the future, and they will be ready to face challenges and obstacles.